Creating and managing sport teams' brands - Richelieu, Andre (Henry Stewart Talks, 2008)
The strategic value of branding, The branding of sport teams and its relevance, The branding of teams in North America vs. Europe, Sport, hip hop and branding, The internationalization of sport teams' brands
Archived at 2022/04/04